Identification of Lines Inducing Male Sterility in Hybrid Maize - Farid, Muh; Azrai, Muhammad; Nur, Amin; Efendy, Roy; Salengke, Salengke; Musa, Yunus; Baharuddin, Baharuddin; Kuswinanti, Tutik; Thamrin, Sulaeha; Suwarno, Willy Bayuardi; Anshori, Muhammad Fuad; Fadhli, Nur; Andayani, Nining; Z, Bunyamin; Mirsam, Hishar; Priyanto, Slamet Bambang; Suriani, Suriani; Novianti, Fira (Hasanuddin University, 2023)
Efficiency and effectiveness in controlling crossbreeding are pivotal in yielding superior hybrid varieties with desired traits such as genetic purity and high productivity. Cytoplasmic Male Sterile (CMS) is a crucial component in hybrid variety assembly. This study aims to identify the genotypes that can induce male sterile lines based on genetic diversity and the level of pollen sterility in the prospective male sterile genotypes tested, consisting of seventeen genotypes. The research findings revealed that the genetic diversity among the seventeen observed male-sterile candidate genotypes tends to vary in quantitative traits. Among the quantitative traits, JHD14 exhibited indications of being a male sterility inducer compared to the other genotypes observed, demonstrating a value of 0.00 g in terms of pollen weight. This is further substantiated by the microscopic examination of JHD14 pollen grains, which displayed 100% sterility.Â